A new time: Bayesian models of an Early Neolithic enclosure in North-Western Denmark - Torfing, Tobias (Danish Journal of Archaeology, 2015)
The article presents the results of the first Bayesian model of a causewayed enclosure from Denmark. 21 samples were dated, some with multiple dates, giving a total of 41 dates. These dates are built into a model which includes archaeological priors in the form of stratigraphy. It is demonstrated that this enclosure can be dated to the same time as the majority of enclosures on the British Isles: the 37th century BC. Together with other early dates for enclosures, it illustrates that enclosure construction was introduced in South Scandinavia as part of a large European expansion of enclosures. With Bayesian modelling, we can provide better answers to more questions, both regarding intrasite chronologies and a wide range of chronological issues.